The Chili’s Politics Revolution after 500 Years of Anthropoceno - Carvajal Bañados, Yuri (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
The article elaborates an analysis of the latest political manifestations of Chile under the perspective of a cosmopolitical crisis that is understood as Anthropocene, a geological epoch determined by human action. It is possible then to call the event a revolution, an expression of a climate-environmental crisis of inescapable validity. In this sense, it is about the inscription of the recent political revolution in the framework of an exhaustion of the categories that have structured the modern political order and that invites to the consideration of a new political scheme where nature, animality, geology and other "not represented" elements take active part of the political and social conformation. It is not the last political movement, but one of the first.
Keywords: Revolution; Anthropocene; Chili